Analysis of Sports Injury Rates Among Athletes Pre-PORA Central Aceh Athletics - Ayu Dewi Setyawati; Muhammad Farhan Aulya (CV Lentera Cendekia Indonesia, 2026)
This study aims to analyze the level of sports injuries, injury management, and factors causing injuries among athletes participating in the Central Aceh Pre-PORA athletics competition. The study uses a quantitative approach with a descriptive research design. The research subjects consisted of 14 athletes selected using total sampling technique. Data collection was conducted through a closed-ended questionnaire based on a Likert scale covering indicators of injury type, causes of injury, post-injury impact, recovery, prevention, and first aid for injuries. Data analysis was performed using percentage techniques. The results showed that the level of sports injuries among Central Aceh Pre-PORA athletes was in the moderate category (86%) and the strong category (14%), while there were no athletes in the very weak, weak, or very strong categories. The most common injuries were minor, such as bruises and muscle cramps, while severe injuries such as fractures and dislocations were not found. The dominant factors causing injuries included poor physical condition and lack of warm-up. In terms of treatment, athletes tended to rely on complete rest, and some used the RICE method and medication. Injury prevention measures are generally well implemented through warm-ups, maintaining physical condition, nutritional management, and the use of adequate equipment. The conclusions of this study indicate that the injury rate among athletes is still within controllable limits, but it is still necessary to strengthen injury prevention and management programs in a more systematic manner in order to maintain the performance and sustainability of athletes' training.